Aluminosilicate or aluminoborosilicate glass compositions and products comprising same

By adjusting the proportion and content of aluminum silicate or aluminum borosilicate in the glass composition in glass compositions, the challenges such as the thermal nature, mechanical properties and size stability of the glass combination in high -resolution display manufacturing Antuction point, higher elastic modulus and lower stress optical coefficient.

CN119330585APending Publication Date: 2025-01-21CORNING INC
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410967700.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-07
Filing Date
2024-07-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing glass compositions face challenges such as thermal properties, mechanical properties and dimensional stability when making high-resolution displays, especially in 8K display technology, requiring higher annealing points, elastic modulus and lower stress optical coefficients. .

Method used

Basic alkali -free glass compositions that have developed an aluminum silicate or aluminum borosilicate, including SIO2, Al2O3, B2O3, MGO, CAO, SRO, and BAO. The annealing point and elastic modulus, while reducing the stress optical coefficient.

Benefits of technology

The annealing point of the glass was increased to more than 775 ° C, the elastic modulus was increased to 82.47GPa to 84.90GPa, and the stress optical coefficient was reduced, suitable for the substrate material for high -resolution display.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330585A_ABST
    Figure CN119330585A_ABST
Patent Text Reader

Abstract

Aluminosilicate or aluminoborosilicate glass compositions and products comprising the same are provided. Such glass compositions are substantially alkali-free and include alkaline earth metal oxides. The glass composition may include a low concentration of boron oxide. The glass compositions exhibit desirable physical and chemical properties, such as improved annealing point (e.g., above 775 DEG C), improved elastic modulus, reduced stress optical coefficient (SOC), and desirable liquidus viscosity. The glass composition is suitable for use as a substrate in a flat panel display device having ultra-high resolution, such as an active matrix liquid crystal display (AMLCD).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims the priority benefit of U.S. application serial number 18 / 224,780 filed on July 21, 2023 under the patent law, which in turn claims the priority benefit of U.S. provisional application serial number 63 / 527,367 filed on July 18, 2023 under the patent law, and also claims the priority benefit of U.S. provisional application serial number 63 / 562,453 filed on March 7, 2024 under the patent law, the contents of which are relied upon by this application and are incorporated herein by reference in their entirety. Technical Field

[0003] The present disclosure relates generally to glass compositions. More specifically, the disclosed subject matter relates to glass compositions suitable for display applications; articles containing the glass compositions; and methods of making the same. Background Art

[0004] Planar or curved substrates made of optically transparent materials such as glass are used in flat panel displays, photovoltaic devices, and other suitable applications. In addition to the requirements for optical transparency, glass compositions also need to meet different challenges depending on the manufacturing process and application.

[0005] For example, the production of liquid crystal displays such as active matrix liquid crystal display devices (AMLCD) is complex, and the properties of the substrate glass are very important. The physical dimensions of the glass substrates used in the production of AMLCD devices need to be strictly controlled. The pull-down sheet drawing process, and in particular the fusion process, can produce glass sheets that can be used as substrates without the need for expensive post-forming finishing operations such as grinding and polishing. However, the fusion process has quite strict restrictions on the properties of the glass, which requires a relatively high liquidus viscosity.

[0006] In the field of liquid crystal displays, it is preferred to use thin film transistors (TFTs) based on polycrystalline silicon because they are able to transport electrons more efficiently. Polycrystalline silicon-based transistors (p-Si) are characterized by having a higher mobility than those based on amorphous silicon (a-Si). This makes it possible to manufacture smaller and faster transistors, ultimately producing brighter and faster displays. One problem with p-Si-based transistors is that their manufacture requires higher process temperatures than those used in the manufacture of a-Si transistors. These temperatures are in the range of 450°C to 600°C, compared to the 350°C peak temperature used in the manufacture of a-Si transistors.

[0007] Glass compositions for display applications need to have good thermal and mechanical properties as well as dimensional stability that meet processing and performance requirements. In addition, diffusion of metal ions into thin film transistors may also damage the transistors. Such diffusion needs to be avoided.

[0008] Display technologies such as televisions are moving toward 8K technology. 8K refers to a horizontal resolution of the order of 8,000 pixels. For example, when an 8K TV has a screen with 7,680 horizontal pixels and 4,320 vertical pixels, such a TV may have a total of about 33 million pixels. 8K technology provides ultra-high resolution. 8K TVs have four times the pixels of 4K TVs with ultra-high definition (UHD) resolution, resulting in clearer and more detailed picture quality. Summary of the invention

[0009] The present disclosure provides aluminosilicate or aluminoborosilicate glass compositions, products containing the same, and methods of making the same. Such glass compositions are substantially alkali-free and include alkaline earth metal oxides. The glass compositions may include low concentrations of boron oxide.

[0010] In one aspect, the present disclosure provides a glass or glass composition. According to some embodiments, the glass or glass composition provided herein comprises the following substances in molar percentages based on oxides:

[0011] SiO2: 68.86-70.87;

[0012] Al2O3: 10.55-13.06;

[0013] B2O3: 0-2.29;

[0014] MgO: 4.82-6.4;

[0015] CaO: 5.31-7.35;

[0016] SrO: 0.3-3.74; and

[0017] BaO: 1.5-4.64.

[0018] Such glass is an aluminosilicate glass or an aluminoborosilicate glass. The glass is substantially alkali-free, as defined by a combined concentration of Li2O, Na2O and K2O of less than 0.1 mol.%, such as less than 0.05 mol.%, less than 0.02%, less than 0.01%, or 0%.

[0019] In some embodiments, B2O3 is within a suitable range. For example, B2O3 is within a range of 0.1 to 2.29 mole percent, within a range of 0.1 to 1.98 mole percent, within a range of 0.5 to 1.90 mole percent, or within a range of 0.5 to 1.60 mole percent.

[0020] In some embodiments, the ratio of RO / Al2O3 is in the range of 1.23 to 1.83, and RO is the sum of the mole percentages of MgO, CaO, SrO, and BaO. For example, in some embodiments, the ratio of RO / Al2O3 is in the range of 1.39 to 1.83. The ratio of RO / Al2O3 may also be in the range of 1.09 to 1.83. The ratio of RO / Al2O3 may also be in the range of 1.47 to 1.83.

[0021] The glass may further comprise 0.01 mol.% to 0.4 mol.% of a chemical fining agent selected from SnO2, As2O3, Sb2O3, Fe2O3, CeO2, MnO2, F, Cl, Br, or any combination thereof. For example, in some embodiments, the chemical fining agent comprises 0.08 mol.% to 0.13 mol.% SnO2.

[0022] The glass has an improved annealing point, for example above 775° C. In some embodiments, the annealing point of the glass is in the range of 775° C. to 810° C., for example in the range of 780° C. to 810° C., in the range of 785° C. to 810° C., or in the range of 780° C. to 791° C.

[0023] The glass also has an improved elastic modulus (Young's modulus). For example, in some embodiments, the elastic modulus of the glass is in the range of 82.47 GPa to 84.90 GPa.

[0024] The glass has a desirable stress optical coefficient (SOC), which is relatively low compared to existing products. For example, in some embodiments, the SOC of the glass provided by the present disclosure is in the range of 27.70 to 29.70.

[0025] According to some embodiments, the glass provided by the present disclosure is an aluminoborosilicate glass and comprises the following substances in mole percentages on an oxide basis:

[0026] SiO2: 68.86-70.87;

[0027] Al2O3: 10.55-13.06;

[0028] B2O3: 0.1-1.98;

[0029] MgO: 4.82-6.4;

[0030] CaO: 5.31-7.35;

[0031] SrO: 0.3-3.74; and

[0032] BaO: 1.5-4.64.

[0033] Glass is essentially alkali-free.

[0034] The RO / Al2O3 ratio of the glass is in the range of 1.23 to 1.83, for example, 1.39 to 1.83 or 1.47 to 1.83, and RO is the sum of the mole percentages of MgO, CaO, SrO and BaO.

[0035] The glass also contains 0.08 mol.% to 0.13 mol.% SnO2 as a chemical fining agent. The annealing point of the glass is in the range of 775°C to 810°C, for example, in the range of 780°C to 810°C, in the range of 785°C to 810°C, or in the range of 780°C to 791°C.

[0036] The elastic modulus of the glass is in the range of 82.47 GPa to 84.90 GPa, and the stress optical coefficient (SOC) is in the range of 27.70 to 29.70.

[0037] In another aspect, the present disclosure provides an article comprising the glass or glass composition described herein. For example, a substrate for a liquid crystal display includes the glass or glass composition described herein.

[0038] In another aspect, the present disclosure provides a flat panel display device comprising at least one plate comprising the glass as described herein. Such a device may also include a polysilicon thin film transistor.

[0039] In another aspect, a method for producing a glass or glass composition as described herein is provided. Such a method comprises at least one step of mixing and melting raw materials in mole percentages based on oxides to provide the oxides. Such a method may also comprise making a sheet comprising the glass composition by a down-drawn sheet manufacturing process or a fusion process.

[0040] The glass composition exhibits desirable physical and chemical properties, such as an improved annealing point (e.g., above 775° C.), an improved elastic modulus, a reduced stress optical coefficient (SOC), and a desirable liquidus viscosity. The glass composition is suitable for use as a substrate in a flat panel display device such as an active matrix liquid crystal display (AMLCD) having ultra-high resolution under, for example, 8K display technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] The present disclosure may be best understood when the following detailed description is read in conjunction with the accompanying drawings. It should be emphasized that, according to convention, the various features of the drawings are not necessarily drawn to scale. On the contrary, the sizes of the various features are arbitrarily enlarged or reduced for clarity. Throughout the specification and drawings, the same reference numerals represent the same features.

[0042] Figure 1The relationship between the RO / Al2O3 ratio and the stress optical coefficient (SOC) of exemplary inventive glass compositions according to some embodiments is depicted in graphical form.

[0043] Figure 2 The relationship between the RO / Al2O3 ratio and the elastic modulus of exemplary inventive glass compositions according to some embodiments is depicted in graphical form.

[0044] Figure 3 Depicted in diagram form Figure 1 to Figure 2 The relationship between stress optical coefficient (SOC) and elastic modulus for exemplary inventive glass compositions is shown. DETAILED DESCRIPTION

[0045] This description of the exemplary embodiments is intended to be read in conjunction with the accompanying drawings, which are to be considered a part of the entire written specification. In the description, relative terms such as "lower", "upper", "horizontal", "vertical", "above", "below", "upward", "downward", "top", and "bottom" and their derivatives (e.g., "horizontally", "downwardly", "upwardly", etc.) should be interpreted as referring to the orientation shown in the drawings described or discussed subsequently. These relative terms are for convenience of description and do not require that the device be constructed or operated in a particular orientation. Terms related to attachment, connection, etc., such as "connected" and "interconnected" refer to relationships in which structures are fastened or attached to each other directly or indirectly through intervening structures, as well as removable or rigid attachments or relationships, unless otherwise explicitly described.

[0046] For the purposes of the following description, it should be understood that the embodiments described below may employ alternative variations and embodiments. It should also be understood that the specific articles, compositions and / or processes described herein are exemplary and should not be considered limiting.

[0047] Open-ended terms such as "include," "including," "contain," "containing," and the like mean "comprising." These open transition phrases are used to introduce an open list of elements, method steps, and the like, and do not exclude additional, uncited elements or method steps. It should be understood that wherever an embodiment is described with the language "comprising," additional similar embodiments described with the terms "consisting of" and / or "consisting essentially of" are also provided.

[0048] The transitional phrase "consisting of" and variations thereof exclude any unrecited elements, steps, or ingredients, except for impurities normally associated therewith.

[0049] The transitional phrase "consists essentially of" or variations such as "consist essentially of" or "consisting essentially of" excludes any unrecited elements, steps, or ingredients, except those that do not materially change the basic or novel properties of the specified method, structure, or composition.

[0050] Unless the context clearly indicates otherwise, in the present disclosure, the singular forms "one", "a kind of" and "the" include plural references, and references to specific numerical values ​​include at least that specific value. When a value is expressed as an approximation by using the antecedent "about", it should be understood that the specific value forms another embodiment. As used herein, "about X" (wherein X is a numerical value) preferably refers to ±10% (including the end value) of the quoted value. For example, the phrase "about 8" preferably refers to a value (including the end value) of 7.2 to 8.8. When present, all ranges are included and can be combined. For example, when quoting a range of "1 to 5", the quoted range should be understood to include a range of "1 to 4", "1 to 3", "1-2", "1-2 and 4-5", "1-3 and 5", "2-5" and the like. In addition, when a list of alternatives is actively provided, such a list can be interpreted as indicating that any alternative can be excluded, for example, by a negative restriction in the claims. For example, when reciting a range of "1 to 5", the recited range may be understood to include any of 1, 2, 3, 4, or 5 that are negatively excluded; thus, the recitation of "1 to 5" may be understood as "1 and 3-5, but not 2", or simply "where 2 is not included". It is intended that any component, element, attribute, or step positively recited herein may be explicitly excluded in the claims, regardless of whether such component, element, attribute, or step is listed as an alternative or recited separately.

[0051] As used herein, the terms "substantially," "substantially," and variations thereof are intended to indicate that the feature being described is equal to or approximately equal to a certain value or description. Additionally, "substantially similar" is intended to mean that two values ​​are equal or approximately equal. In some embodiments, "substantially similar" may mean that the values ​​are within about 10% of each other, such as within about 5% of each other, or within about 2% of each other.

[0052] The present disclosure provides aluminosilicate or aluminoborosilicate glass compositions, products (such as articles or devices) containing the same, and methods of making the glass compositions and products. Such glass compositions are substantially alkali-free and include alkaline earth metal oxides. The glass compositions may contain low concentrations of boron oxide. For example, the boron oxide is in the range of 0 to 2.67 or 0 to 2.29 mole percent.

[0053] In some embodiments, the substrate is optically transparent.Examples of substrates include, but are not limited to, flat or curved glass plates.

[0054] Unless otherwise expressly stated, the terms "glass article" or "glass" as used herein should be understood to cover any object made entirely or partially of glass. Glass articles include monolithic substrates, or laminates of glass and glass, glass and non-glass materials, glass and crystalline materials, and glass and glass ceramics (including amorphous and crystalline phases). Unless otherwise expressly stated, the terms "glass" and "glass composition" as used herein are interchangeable.

[0055] Glass articles such as glass sheets can be flat or curved and transparent or substantially transparent. As used herein, the term "transparent" is intended to mean that the transmittance of an article having a thickness of about 1 mm in the visible region of the spectrum (400-700 nm) is greater than about 85%. For example, an exemplary transparent glass sheet may have a transmittance greater than about 85% in the visible light range, such as a transmittance greater than about 90%, greater than about 95%, or greater than about 99%, including all ranges and sub-ranges therebetween. According to various embodiments, the transmittance of the glass article in the visible light region may be less than about 50%, such as less than about 45%, less than about 40%, less than about 35%, less than about 30%, less than about 25%, or less than about 20%, including all ranges and sub-ranges therebetween. In certain embodiments, the exemplary glass sheet may have a transmittance greater than about 50% in the ultraviolet (UV) region (100-400 nm), such as greater than about 55%, greater than about 60%, greater than about 65%, greater than about 70%, greater than about 75%, greater than about 80%, greater than about 85%, greater than about 90%, greater than about 95%, or greater than about 99%, including all ranges and sub-ranges therebetween.

[0056] Exemplary glasses may include, but are not limited to, aluminosilicates and aluminoborosilicates. The glass article may optionally be strengthened. In some embodiments, the glass article may be mechanically strengthened by exploiting the mismatch in thermal expansion coefficients between portions of the glass article to create regions of compressive stress and a central region exhibiting tensile stress. In some embodiments, the glass article may be thermally strengthened by heating the glass to a temperature above the glass transition point and then rapidly quenching. In some other embodiments, the glass article may be chemically strengthened by ion exchange.

[0057] In the embodiments of the glass compositions described herein, unless otherwise specified, the concentrations of constituent components (eg, SiO 2 , Al 2 O 3 , etc.) are expressed as mole percent (mol. %) on an oxide basis.

[0058] The terms "free" and "substantially free" when used to describe the concentration and / or absence of a particular constituent in a glass composition mean that the constituent is not intentionally added to the glass composition. However, the glass composition may contain trace amounts of the constituent as contaminants or impurities in an amount less than 0.01 mol.%.

[0059] In some embodiments, the glass compositions provided herein are alkali-free or substantially alkali-free. Unless otherwise expressly stated, the terms "alkali-free" or "substantially alkali-free" for glass compositions used herein should be understood to encompass glass compositions having a combined concentration of Li2O, Na2O, and K2O of less than 0.1 mol.%, such as less than 0.05 mol.%, less than 0.02 mol.%, less than 0.01 mol.%, or 0 mol.%.

[0060] In the glass compositions described herein, the ratio of RO / Al2O3 is the ratio of the sum of the molar percentages of RO to the molar percentage of Al2O3, wherein RO includes MgO, CaO, SrO, BaO, and ZnO. When the composition does not contain ZnO, RO refers to the molar percentage of the alkaline earth metal oxide, and the ratio of RO / Al2O3 is the same as the ratio of (MgO+CaO+SrO+BaO) / Al2O3.

[0061] As used herein, the term "softening point" refers to the viscosity of a glass composition at 1×10 7.6 The temperature during parking.

[0062] As used herein, the term "annealing point" refers to the viscosity of the glass composition at 1×10 13 The temperature during parking.

[0063] As used herein, the terms "strain point" and "T 应变 " refers to the viscosity of the glass composition of 3 × 10 14 The temperature during parking.

[0064] The liquidus temperature of glass (T liq ) is the temperature (°C) above which no crystalline phase can coexist in equilibrium with the glass. The liquidus viscosity is the viscosity of the glass at the liquidus temperature.

[0065] As used herein, the term "CTE" refers to the coefficient of thermal expansion of a glass composition in the temperature range of about room temperature (RT) to about 300°C. The linear coefficient of thermal expansion (CTE) in the temperature range of 25-300°C is expressed in ×10 -7 / ℃ and measured according to ASTM standard E228.

[0066] Young's modulus values ​​and shear modulus (in GPa) and Poisson's ratio are determined using resonant ultrasonic spectroscopy techniques of the general type specified in ASTM E1875-00e1. The terms "Young's modulus" and "elastic modulus" are interchangeable.

[0067] Fracture toughness can be measured using methods known in the art, for example, using a chevron notch, a short bar, a notched beam, etc., in accordance with ASTM C1421-10, "Standard Test Methods for Determination of Fracture Toughness of Advanced Ceramics at Ambient Temperature".

[0068] Stress-optical coefficient (SOC) values ​​may be measured as described in Procedure C (Glass Disk Method) of ASTM Standard C770-16 entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient."

[0069] As the industry moves toward 8K display panels, thicker copper wires will be required. Copper has a high CTE, and thicker copper wires will result in higher tensile film stress, causing both the sheet and the panel to warp. This can interfere with processing yields. Referring to Stoney's formula shown in Equation 1 below,

[0070]

[0071] R is the radius of curvature, E is Young's modulus, t is the cantilever thickness, is Poisson's ratio, and σ is the resulting surface stress.

[0072] It can be seen that the amount of strain is proportional to E (elastic modulus). Therefore, for a given stress, a higher modulus (E) will result in lower strain / warp.

[0073] In addition, panel manufacturers are moving toward borderless panel designs, which leads to excessive stress-induced light leakage (mura). The mura intensity is related to the glass stress optical coefficient (SOC) through Equation 2:

[0074] Mura intensity ∝(SOC X t) 2 (Formula 2),

[0075] where t is the thickness of the glass sheet.

[0076] It is expected that the reduction in glass SOC will lead to an improvement in mura or a reduction in light leakage.

[0077] In the present disclosure, the glass is designed to increase physical properties such as Young's modulus and reduce stress optical coefficient (SOC). In addition, the glass is designed to increase the annealing point and obtain the desired liquidus temperature. An existing product Corning Astra glass was selected as a benchmark for the development described in the present disclosure.

[0078] Corning Astra Glass (abbreviated as "Astra" or "Astra Glass"), as an existing product, is a precision-engineered glass substrate that provides the higher pixel density required for high-performance displays required by panel manufacturers to meet consumer demand for brighter, faster, more lifelike images. Astra Glass has an optimal combination of low total pitch variation (TPV), low total thickness variation (TTV), and low sag (sag), and is thermally and dimensionalally stable enough to operate properly over a wide range of processing temperatures, including oxide thin-film transistor (TFT) backplane manufacturing processes.

[0079] In the present disclosure, glasses are developed whose Young's modulus is increased compared to Astra glass (81.7 GPa) and whose SOC is reduced compared to Astra glass (30.0). The annealing point of these glasses is also designed to be higher than Astra glass (775°C), which is ideal because it improves the stress relaxation properties of the glass relative to Astra glass, thereby improving TPV (total pitch variation). It is also desirable to keep the 200P temperature between Astra glass (1,633°C) and Corning Lotus NXT glass (1,683°C), and to keep the 35kP temperature between Astra glass (1,259°C) and Lotus NXT (1,296°C).

[0080] Table 1 shows exemplary ranges of component contents and properties of the designed glasses, including minimum and maximum values ​​of component contents and properties in exemplary glass compositions. As can be seen from Table 1, the Young's modulus of these glasses is ≥1% higher than that of Astra glass, and the SOC is ≥1% lower than that of Astra glass. It can also be seen from the table that the annealing points of these glasses are about 5-10°C higher than those of Astra glass.

[0081] Table 1.

[0082]

[0083]

[0084] In Table 1, B2O3 can be in a suitable range. For example, B2O3 is in the range of 0.1 to 2.29 mole percent, in the range of 0.1 to 1.98 mole percent, in the range of 0.5 to 1.90 mole percent, or in the range of 0.5 to 1.60 mole percent. The ratio of RO / Al2O3 can be in the range of 1.23 to 1.83, and RO is the sum of the mole percentages of MgO, CaO, SrO, BaO, and optionally ZnO. For example, in some embodiments, the ratio of RO / Al2O3 is in the range of 1.39 to 1.83. The ratio of RO / Al2O3 can also be in the range of 1.09 to 1.83. In some embodiments, the SrO content is less than 1 mole percent. In Table 1, SnO2 can be replaced with another suitable chemical fining agent as described herein.

[0085] According to some embodiments, the glasses or glass compositions provided herein include the following substances in mole percentages on an oxide basis:

[0086] SiO2: 68.86-70.87;

[0087] Al2O3: 10.55-13.06;

[0088] B2O3: 0-2.29;

[0089] MgO: 4.82-6.4;

[0090] CaO: 5.31-7.35;

[0091] SrO: 0.3-3.74; and

[0092] BaO: 1.5-4.64.

[0093] Such glass is an aluminosilicate glass or an aluminoborosilicate glass. The glass is alkali-free or substantially alkali-free, as defined by a combined concentration of Li2O, Na2O and K2O of less than 0.1 mol.%, such as less than 0.05 mol.%, less than 0.02 mol.%, less than 0.01 mol.%, or 0%.

[0094] In some embodiments, B2O3 is within a suitable range. For example, B2O3 is within a range of 0.1 to 2.29 mole percent, within a range of 0.1 to 1.98 mole percent, within a range of 0.5 to 1.90 mole percent, or within a range of 0.5 to 1.60 mole percent.

[0095] In some embodiments, the ratio of RO / Al2O3 is in the range of 1.23 to 1.83, and RO is the sum of the mole percentages of MgO, CaO, SrO, and BaO. For example, in some embodiments, the ratio of RO / Al2O3 is in the range of 1.39 to 1.83. The ratio of RO / Al2O3 may also be in the range of 1.09 to 1.83.

[0096] The glass may further comprise 0.01 mol.% to 0.4 mol.% of a chemical fining agent selected from SnO2, As2O3, Sb2O3, Fe2O3, CeO2, MnO2, F, Cl, Br, or any combination thereof. For example, in some embodiments, the chemical fining agent comprises 0.08 mol.% to 0.13 mol.% SnO2.

[0097] The glass has an improved annealing point, for example above 775° C. In some embodiments, the annealing point of the glass is in the range of 775° C. to 810° C., for example in the range of 780° C. to 810° C. or in the range of 785° C. to 810° C.

[0098] The glass also has an improved elastic modulus (Young's modulus). For example, in some embodiments, the elastic modulus of the glass is in the range of 82.47 GPa to 84.90 GPa.

[0099] The glass has a desired stress optical coefficient (SOC) that is relatively low compared to existing products. For example, the SOC of the glass is in the range of 27.70 to 29.70.

[0100] The liquidus viscosity of the glass is in a range of 69,000 poise to 276,000 poise, such as 90,000 poise to 276,000 poise, 100,000 poise to 276,000 poise, 150,000 poise to 250,000 poise, or 200,000 poise to 250,000 poise.

[0101] The glass also has suitable ranges of other properties, such as those shown in Table 1.

[0102] According to some embodiments, the glass provided by the present disclosure is an aluminoborosilicate glass and comprises the following substances in mole percentages on an oxide basis:

[0103] SiO2: 68.86-70.87;

[0104] Al2O3: 10.55-13.06;

[0105] B2O3: 0.1-1.98;

[0106] MgO: 4.82-6.4;

[0107] CaO: 5.31-7.35;

[0108] SrO: 0.3-3.74; and

[0109] BaO: 1.5-4.64.

[0110] The glass is substantially alkali-free, defined by the combined concentration of Li2O, Na2O and K2O being less than 0.1 mol.%.

[0111] The RO / Al2O3 ratio of the glass is in the range of 1.23 to 1.83, for example 1.39 to 1.83, and RO is the sum of the mole percentages of MgO, CaO, SrO and BaO.

[0112] The glass also contains 0.08 mol.% to 0.13 mol.% SnO2 as a chemical refining agent.The annealing point of the glass is in the range of 775°C to 810°C, for example in the range of 780°C to 810°C or in the range of 785°C to 810°C.

[0113] The elastic modulus of the glass is in the range of 82.47 GPa to 84.90 GPa, and the stress optical coefficient (SOC) is in the range of 27.70 to 29.70.

[0114] The glass has other desirable properties as described herein.

[0115] The inventors surprisingly found that compositions with specific oxide contents, such as low levels of B2O3, particularly when combined with relatively high MgO contents and specific RO / Al2O3 ratios, can provide glasses with suitably high values ​​for higher annealing points, higher moduli, and lower stress optical coefficients (SOCs) compared to existing products such as Astra Glass. The compositions described herein provide filled glass structures that provide lower stress optical coefficients.

[0116] In embodiments of the glass compositions described herein, SiO2 is the largest component in the composition and is therefore a major component of the glass network. SiO2 enhances the chemical durability of the glass, particularly the resistance of the glass composition to acid decomposition, and provides a desired liquidus temperature or liquidus viscosity. The resulting chemical durability makes the glass suitable for use as a flat panel display glass (e.g., AMLCD glass). Therefore, a high SiO2 concentration is generally required. However, if the SiO2 content is too high, the formability of the glass may be reduced because a higher concentration of SiO2 increases the difficulty of melting the glass, which in turn has an adverse effect on the formability of the glass.

[0117] In the embodiments described herein, the glass composition includes SiO2 in an amount greater than or equal to about 68.86 mol.% and less than or equal to about 70.87 mol.%. In some embodiments, SiO2 is present in the glass composition in an amount greater than or equal to about 69 mol.% and less than or equal to about 70.5 mol.%. In some other embodiments, SiO2 is present in the glass composition in an amount greater than or equal to about 69 mol.% and less than or equal to about 70 mol.%.

[0118] The glass composition described herein also includes Al2O3. Al2O3 at a concentration equal to or greater than 10.55 mole percent provides the glass with a low liquidus temperature and high viscosity, resulting in a high liquidus viscosity. The use of at least 10.55 mole percent of Al2O3 also increases the annealing point and modulus of the glass. Al2O3 increases the sensitivity of the glass to ion exchange strengthening. In addition, the addition of Al2O3 to the composition reduces the tendency of alkaline components (such as Na and K) (if any) to leach out of the glass, and therefore, the addition of Al2O3 increases the resistance of the composition to hydrolytic degradation. In addition, the addition of Al2O3 can also increase the softening point of the glass, thereby reducing the formability of the glass.

[0119] The glass compositions described herein include Al2O3 in an amount greater than or equal to about 10.55 mol.% and less than or equal to about 13.06 mol.%. In some embodiments, the amount of Al2O3 in the glass composition is greater than or equal to about 11 mol.% and less than or equal to about 13 mol.%. In some other embodiments, the amount of Al2O3 in the glass composition is greater than or equal to about 11 mol.% and less than or equal to about 12.5 mol.%.

[0120] In some embodiments, in order to make the ratio of RO / Al2O3 in the range of 1.09 to 1.83, and RO is the sum of the molar percentages of MgO, CaO, SrO and BaO, when ZnO is not added, the content of Al2O3 is kept below 13.06%. For example, the ratio of RO / Al2O3 is in the range of 1.39 to 1.83 or in the range of 1.23 to 1.83.

[0121] B2O3 is both a glass former and a flux that helps melt and lowers the melting temperature. It has an effect on both the liquidus temperature and viscosity. Increasing B2O3 can be used to increase the liquidus viscosity of the glass. In order to achieve these effects, the glass composition of one or more embodiments may have a B2O3 concentration equal to or greater than 0.1 mole percent. As discussed above with respect to SiO2, glass durability is very important for LCD applications. Durability can be controlled to a certain extent by increasing the concentration of alkaline earth oxides, and significantly reduced by increasing the B2O3 content. The annealing point decreases with the increase of B2O3, so it may be helpful to keep the B2O3 content low relative to its typical concentration in amorphous silicon substrates. Therefore, in some embodiments, the B2O3 concentration of the glass composition is in the range of about 0.0 to 2.29 mole percent. Surprisingly, it was found that this low content of B2O3 increases the elastic modulus of the resulting glass.

[0122] For example, B2O3 is in the range of 0.1 to 2.29 mole percent, in the range of 0.1 to 1.98 mole percent, in the range of 0.5 to 1.90 mole percent, or in the range of 0.5 to 1.60 mole percent. It was unexpectedly found that the combination of such lower levels of B2O3 concentration with the range of other oxides surprisingly provides excellent properties of the glass, such as an annealing point above 775°C, improved modulus, and reduced stress optical coefficient. These properties make the glass suitable for ultra-high resolution display applications such as 8K display technology.

[0123] In addition to the glass formers (SiO2, Al2O3 and B2O3), the glasses described herein also contain alkaline earth oxides. In some embodiments, four alkaline earth oxides are present in the glass composition, such as MgO, CaO, BaO and SrO. In another embodiment, SrO is replaced by BaO. Alkaline earth oxides provide various properties that are important for melting, clarification, forming and final use of the glass. Therefore, in order to improve the performance of the glass in these aspects, in one embodiment, the ratio of (MgO+CaO+SrO+BaO) / Al2O3 is greater than or equal to 1.09. As this ratio increases, the viscosity tends to drop more than the liquidus temperature, so it becomes increasingly difficult to obtain a suitably high liquidus viscosity value. Therefore, in another embodiment, the ratio (MgO+CaO+SrO+BaO) / Al2O3 is less than or equal to 1.83.

[0124] The reduced RO concentration and increased Al2O3 content are also factors that contribute to providing a filled glass structure, which reduces the stress optical coefficient of the resulting glass.

[0125] For certain embodiments, the alkaline earth oxides may be considered as components that are effectively single constituents. This is because their effects on viscoelastic properties, liquidus temperature, and liquidus phase relationships are qualitatively more similar to each other than their effects on the glass-forming oxides SiO2, Al2O3, and B2O3. However, the alkaline earth oxides CaO, SrO, and BaO can form feldspar minerals, particularly anorthite (CaAl2Si2O8) and celsium feldspar (BaAl2Si2O8) and their strontium-containing solid solutions, but the content of MgO in these crystals is not significant. Therefore, when the feldspar crystals are already in the liquidus phase, the super addition of MgO can be used to stabilize the liquid relative to the crystals, thereby reducing the liquidus temperature. At the same time, the viscosity curve generally becomes steeper, reducing the melting temperature, while having little effect on the low temperature viscosity. In this sense, the addition of a small amount of MgO is beneficial to melting because it can reduce the melting temperature; it is beneficial to forming because it can reduce the liquidus temperature and increase the liquidus viscosity while maintaining a high annealing point, thereby reducing the compaction degree. Thus, in various embodiments, the glass composition includes MgO in an amount ranging from about 4.8 mol percent to about 6.4 mol percent.

[0126] In addition to MgO, the glass composition also includes CaO in the range of about 5.31 mol % to about 7.35 mol %, SrO in the range of about 0.3 mol % to about 3.74 mol %, and BaO in the range of about 1.5 mol % to about 4.64 mol %. These alkaline earth metal oxides in combination with other oxides including SiO2, Al2O3, and B2O3 in specific molar percentages provide the excellent properties described herein.

[0127] The presence of calcium oxide in the glass composition can produce a low liquidus temperature (high liquidus viscosity), a high annealing point and modulus, and a CTE in the most desirable range for flat panel applications, particularly AMLCD applications. The calcium oxide also helps improve chemical durability and is relatively inexpensive as a batch material compared to other alkaline earth oxides. However, at high concentrations, CaO increases density and CTE. In addition, at sufficiently low SiO2 concentrations, CaO can stabilize anorthite, thereby reducing liquidus viscosity. Therefore, in one embodiment, the CaO concentration can be between 5.31 mole percent and 7.35 mole percent.

[0128] Both SrO and BaO can result in low liquidus temperatures (high liquidus viscosities), and therefore, the glasses described herein will contain at least these two oxides. However, the selection and concentration of these oxides are selected to avoid increases in CTE and density and decreases in modulus and annealing point. The relative proportions of SrO and BaO can be balanced to obtain a combination of appropriate physical properties and liquidus viscosities so that the glass can be formed by a down-draw process. In some embodiments, the glass contains SrO in the range of about 0.3 mole percent to about 3.74 mole percent, and BaO in the range of about 1.5 mole percent to about 4.64 mole percent. In some embodiments, SrO is less than 1 mole percent.

[0129] In addition to meltability and annealing point considerations, for AMLCD applications, the CTE of the glass should be compatible with the CTE of silicon. To achieve such CTE values, the exemplary glass controls the RO content of the glass. For a given Al2O3 content, controlling the RO content is equivalent to controlling the RO / Al2O3 ratio.

[0130] In one or more embodiments, the present disclosure provides glasses for AMLCD applications having a coefficient of thermal expansion (CTE) (22-300° C.) of about 33.3 x 10 -7 / ℃ to about 40.0x10 -7 / ℃ or in the range of about 35x10 -7 / ℃ to about 40x10 -7 / ℃ range.

[0131] Glass can be formed by a down-draw process (e.g., a fusion process), which means that the liquidus viscosity of the glass needs to be relatively high. Individual alkaline earths play an important role in this regard, and they may destabilize the crystalline phase that would otherwise form. BaO and SrO are particularly effective in controlling the liquidus viscosity and are included in the exemplary glasses at least for this purpose. As shown in the examples given below, a combination of four alkaline earth oxides will produce a glass with a high liquidus viscosity, where the sum of the alkaline earths meets the RO / Al2O3 ratio constraints required to achieve a low melting temperature, a high annealing point, and a suitable CTE.

[0132] In addition to the above components, the glass compositions described herein may also include various other oxides to adjust various physical, melting, clarifying and forming properties of the glass. Examples of such other oxides include, but are not limited to, TiO2, MnO, Fe2O3, ZnO, Nb2O5, MoO3, ZrO2, Ta2O5, WO3, Y2O3, La2O3 and CeO2. In some embodiments, these oxides are not added. In some embodiments, the amount of each of these oxides may be less than or equal to 0.5 mole percent, such as less than 0.1 mole percent, and their total combined concentration may be less than or equal to 2.0 mole percent, such as less than 1.0 mole percent.

[0133] The glass compositions described herein may also include various contaminants associated with the batch materials and / or introduced into the glass by the melting, refining and / or forming equipment used to produce the glass, particularly Fe2O3 and ZrO2. The glass may also contain SnO2 as a result of Joule melting using tin oxide electrodes and / or by the dosing of tin-containing materials such as SnO2, SnO, SnCO3, and SnC2O2.

[0134] As2O3 and Sb2O3 are effective high temperature fining agents for AMLCD glass. However, due to their toxicity, they require special handling during the glass manufacturing process.

[0135] Example

[0136] The following examples are listed below to illustrate the methods and results according to the disclosed subject matter. These examples are not intended to include all embodiments of the subject matter disclosed herein, but are intended to illustrate representative methods and results. These examples are not intended to exclude equivalents and variants of the present disclosure, which should be apparent to those skilled in the art.

[0137] Efforts have been made to ensure the accuracy of numbers (e.g., amounts, temperatures, etc.), but some errors and deviations should be considered. Unless otherwise indicated, temperatures are in ° C. or are room temperature, and pressures are equal to or close to atmospheric pressure. The compositions themselves are given as mole percentages based on oxides and have been standardized to 100%. There are many variations and combinations of reaction conditions, such as component concentrations, temperatures, pressures, and other reaction ranges and conditions that can be used to optimize the product purity and yield obtained from the process. Only reasonable routine experiments are required to optimize these process conditions.

[0138] The glass properties listed in the table are determined according to conventional techniques in the glass field. Therefore, the linear coefficient of thermal expansion (CTE) in the temperature range of 25-300°C is expressed as x10 -7 / ° C, and the annealing point is expressed in ° C. These are determined by the fiber elongation technique (ASTM reference E228-85 and C336 respectively). The density (in grams / cm 3 The melting temperature (defined as the temperature at which the glass melt exhibits a viscosity of 200 poise) in units of °C was calculated by fitting the high temperature viscosity data measured by the rotating cylinder viscometry method (ASTM C965-81) using the Fulcher equation.

[0139] The viscosity of glass at elevated temperatures is measured in accordance with ASTM C965-96 (2012) entitled "Standard Practice for Measuring Viscosity of Glass Above the Softening Point". As used herein, the "Vogel-Fulcher-Tamman" (VFT) relationship describes the temperature dependence of viscosity and is represented by the following formula:

[0140] logη=A+B T-To

[0141] Where η is the viscosity. To determine VFT A, VFT B and VFT T o , the viscosity of the glass composition is measured within a given temperature range. The raw data of viscosity and temperature are then fitted to the VFT formula by least squares fitting to obtain A, B and T o Using these values, the viscosity point at any temperature above the softening point can be calculated (eg, 200 Poise (P) temperature, 35,000P temperature, and 200,000P temperature).

[0142] The liquidus temperature (in °C) of the glass is measured using the standard gradient boat liquidus method of ASTM C829-81. This involves placing crushed glass particles in a platinum boat, placing the boat in a kiln with gradient temperature zones, heating the boat in the appropriate temperature zones for 24 hours, and determining by microscopic examination the highest temperature at which crystals appear inside the glass. More specifically, the glass sample is removed from the Pt boat in one piece and examined using a polarized light microscope to determine the location and nature of crystals formed at the Pt and air interface and inside the sample. Because the gradient of the kiln is very well defined, the relationship between temperature and location can be well estimated to within 5-10 °C. The temperature at which crystals are observed inside the sample is taken as the liquidus of the glass (for the corresponding test period). Tests are sometimes run for longer periods of time (e.g., 72 hours) to observe slower growth phases. The liquidus viscosity (in poise) is determined from the liquidus temperature and the coefficients of Fulcher's formula.

[0143] Values ​​of Young's modulus and shear modulus (in GPa) and Poisson's ratio were determined using a resonant ultrasonic spectroscopy technique of the general type specified in ASTM E1875-00el.

[0144] Stress-optical coefficient (SOC) values ​​may be measured as described in Procedure C (Glass Disk Method) of ASTM Standard C770-16 entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient."

[0145] Table 2-12 shows exemplary glasses including samples 1-71. As can be seen from Table 2-12, the exemplary glasses have such density, annealing point, Young's modulus, CLE, and stress optical coefficient (SOC) that the glasses are suitable for display applications, such as AMLCD substrate applications, and more specifically for low temperature polysilicon and oxide thin film transistor applications. Although not shown in Table 2-12, the durability of the glasses in acidic and alkaline media is similar to that of glasses obtained from commercial AMLCD substrates, and thus is suitable for AMLCD applications. The exemplary glasses can be formed using a down-draw technique and are compatible with fusion processes, in particular, by the above-mentioned criteria.

[0146] The exemplary glasses in the table were prepared using commercial sand as the silica source, ground so that 90% by weight of the glass would pass through a standard U.S. 100 mesh sieve. Alumina was the source of alumina, periclase was the source of MgO, limestone was the source of CaO, strontium carbonate, strontium nitrate, or a mixture thereof was the source of SrO, barium carbonate was the source of BaO, and tin (IV) oxide was the source of SnO2. The raw materials were thoroughly mixed, loaded into a platinum container suspended in a kiln heated by a silicon carbide heating rod, melted at a temperature of 1600 to 1650°C and stirred for several hours to ensure homogeneity, and delivered through a hole in the bottom of the platinum container. The resulting glass mass was annealed at or near the annealing point, and the physical, viscosity, and liquidus properties were determined using various experimental methods.

[0147] These methods are not exclusive, and the glasses of Tables 1-12 can be prepared using standard methods well known to those skilled in the art. Such methods include continuous melting processes, such as those carried out in a continuous melting process, wherein the melter used in the continuous melting process is heated by gas, electricity, or a combination thereof.

[0148] Raw materials suitable for producing exemplary glasses include commercial sand as a source of SiO2; aluminum oxide, aluminum hydroxide, hydrated aluminum oxide, and various aluminosilicates, nitrates, and halides as a source of Al2O3; boric acid, anhydrous boric acid, and boric oxide as a source of B2O3; periclase, dolomite (also a source of CaO), magnesium oxide, magnesium carbonate, magnesium hydroxide, and various forms of magnesium silicates, aluminosilicates, nitrates, and halides as a source of MgO; limestone, aragonite, dolomite (also a source of MgO), wollastonite, and various forms of calcium silicates, aluminosilicates, nitrates, and halides as a source of CaO; and oxides, carbonates, nitrates, and halides of strontium and barium. If a chemical fining agent is desired, tin can be added as SnO2, as a mixed oxide with another major glass component (e.g., CaSnO3), or under oxidizing conditions as SnO, tin oxalate, tin halide, or other tin compounds known to those skilled in the art.

[0149] The glasses in Tables 2-12 contain SnO2 as a clarifier, but other chemical clarifiers may also be used to obtain glass of sufficient quality for TFT substrate applications. For example, the exemplary glass may employ any one or combination of As2O3, Sb2O3, CeO2, Fe2O3, and halides as intentional additions to promote clarification, and any of these may be used in combination with the SnO2 chemical clarifier shown in the examples. Among them, As2O3 and Sb2O3 are generally considered hazardous materials and are controlled in waste streams that may be generated during glass manufacturing or during TFT panel processing. Therefore, it is desirable to limit the concentration of As2O3 and Sb2O3, either individually or in combination, to no more than 0.005 mol%.

[0150] In addition to the elements intentionally added to the exemplary glasses, almost all stable elements in the periodic table are present in the glass at some level, either through low-level contamination in the raw materials, through high-temperature attack of refractory materials and precious metals during manufacturing, or through the intentional introduction of low-level elements to fine-tune the properties of the final glass. For example, zirconium can be introduced as a contaminant through interaction with zirconium-rich refractory materials. As another example, platinum and rhodium can be introduced through interaction with precious metals. As another example, iron can be introduced into the raw materials as an impurity, or it can be intentionally added to enhance control of gaseous inclusions. As another example, manganese can be introduced to control color or enhance control of gaseous inclusions.

[0151] As another example, for combined concentrations of Li2O, Na2O, and K2O, alkali metals may be present as impurity components at levels up to about 0.1 mol%.

[0152] Hydrogen inevitably forms in the form of hydroxyl anions OH- , and its presence can be determined by standard infrared spectroscopy techniques. Dissolved hydroxide ions have a significant and nonlinear effect on the annealing point of the exemplary glass, so in order to obtain the desired annealing point, it may be necessary to adjust the concentration of the main oxide component to compensate. The concentration of hydroxide ions can be controlled to some extent by selecting the raw materials or selecting the melting system. For example, boric acid is a major source of hydroxyl groups, and replacing boric acid with boric oxide can be a useful means of controlling the concentration of hydroxyl groups in the final glass. The same applies to other potential raw materials, including hydroxide ions, hydrates, or compounds containing physically adsorbed or chemically adsorbed water molecules. If a burner is used in the melting process, then hydroxide ions can also be introduced through the combustion products of the combustion of natural gas and related hydrocarbons, so it may be necessary to transfer the energy used in the melting from the burner to the electrode to compensate. Alternatively, one can use an iterative process to adjust the main oxide component to compensate for the deleterious effects of dissolved hydroxide ions.

[0153] Sulfur is commonly present in natural gas and is also an impurity component of many carbonate, nitrate, halide and oxide raw materials. In the form of SO2, sulfur can be a source of troublesome gaseous inclusions. The tendency to form SO2-rich defects can be controlled to a great extent by controlling the sulfur content of the raw materials and by adding low levels of relatively reducing multivalent cations to the glass matrix. While not wishing to be bound by theory, it appears that SO2-rich gaseous inclusions are primarily formed by reducing sulfate (SO4) dissolved in the glass. = ) is produced.

[0154] Increasing the concentration of barium in the exemplary glass appears to increase the retention of sulfur in the glass during the early stages of melting, but as noted above, barium is required to achieve a low liquidus temperature and thus a high T. 35k -T liq and high liquidus viscosity. Intentionally controlling the sulfur level in the raw materials to a lower level is a useful means of reducing dissolved sulfur (possibly sulfate) in the glass. In particular, sulfur is preferably less than 200 ppm by weight in the batch, more preferably less than 100 ppm by weight in the batch.

[0155] The reduced multivalent states can also be used to control the tendency of the exemplary glasses to form SO2 bubbles. While not wishing to be bound by theory, these elements act as potential electron donors, suppressing the electromotive force of sulfate reduction. Sulfate reduction can be written as a half-reaction such as

[0156] SO4 = →SO2+O2+2e -

[0157] where e - represents electrons. The "equilibrium constant" for the half-reaction is

[0158] K eq =[SO2][O2][e - ] 2 / [SO4 = ]

[0159] The brackets indicate chemical activity. Ideally, one would like to force the reaction so that SO2, O2, and 2e - Sulfate is formed. Adding nitrates, peroxides, or other oxygen-rich raw materials may help, but may also be detrimental to the reduction of sulfates in the early stages of melting, which may offset the benefits of adding them. SO2 has very low solubility in most glasses, so it is impractical to add to the glass melt. Electrons can be "added" by reducing multivalent states. For example, ferrous iron (Fe 2+ ) is represented by the appropriate electron-donating half-reaction

[0160] 2Fe 2+ →2Fe 3+ +2e -

[0161] This "activity" of electrons can force the sulfate reduction reaction to proceed to the left, thereby stabilizing the SO4 in the glass. = Suitable reducing polyvalents include, but are not limited to, Fe 2+ , Mn 2+ Sn 2+ , Sb 3+ 、As 3+ 、V 3+ 、Ti 3+ and others familiar to those skilled in the art. In each case, it is important to minimize the concentration of such components to avoid deleterious effects on the color of the glass or, in the case of As and Sb, to avoid adding such components at levels high enough to avoid complicating waste management in the end user's process.

[0162] In addition to the major oxide components of the exemplary glasses and the minor or impurity components described above, there may be varying levels of halides present, either as contaminants introduced by the choice of raw materials or as intentional components used to eliminate gaseous inclusions in the glass. Halides may be added at levels of about 0.4 mol% or less as fining agents, but it is generally desirable to use lower amounts if possible to avoid corrosion of exhaust gas treatment equipment. In some embodiments, the concentration of the individual halide elements is less than about 200 ppm by weight for each individual halide, or less than about 800 ppm by weight for the sum of all halide elements.

[0163] In addition to these major oxide components, minor and impurity components, multivalents and halide fining agents, it may be useful to add other colorless oxide components in low concentrations to achieve desired physical, optical or viscoelastic properties. Such oxides include, but are not limited to, TiO2, ZrO2, HfO2, Nb2O5, Ta2O5, MoO3, WO3, ZnO, In2O3, Ga2O3, Bi2O3, GeO2, PbO, SeO3, TeO2, Y2O3, La2O3, Gd2O3 and others known to those skilled in the art. By an iterative process of adjusting the relative proportions of the major oxide components of the exemplary glasses, such colorless oxides may be added to levels up to about 2 mol% without affecting the annealing point, T 35k -T liq or liquidus viscosity has an unacceptable effect.

[0164] The samples and their data are summarized in Tables 2-12. In Tables 2-12, "EXG" represents an existing product Corning EAGLE from Corning Incorporated (Corning, NY). LCD glass substrate, and "Astra" represents another existing product Corning Astra glass from Corning Incorporated, as described above.

[0165] Table 2 shows examples of glass (samples 1-8)

[0166] Table 2.

[0167]

[0168]

[0169]

[0170] Table 3 shows examples of glass (samples 9-17) Table 3.

[0171]

[0172]

[0173]

[0174]

[0175] Table 4 shows examples of glass (samples 18-25) Table 4.

[0176]

[0177]

[0178]

[0179] Table 5 shows examples of glass (samples 26-32) Table 5.

[0180]

[0181]

[0182]

[0183] Table 6 shows examples of glass (Samples 33-37).

[0184] Table 6.

[0185]

[0186]

[0187]

[0188] Table 7 shows examples of glass (samples 38-44) Table 7.

[0189]

[0190]

[0191]

[0192]

[0193] Table 8 shows examples of glass (samples 45-48) Table 8.

[0194]

[0195]

[0196]

[0197] In Table 8, although samples 45 and 46 show excellent performance, they can still be considered as comparative samples of the present disclosure. According to some embodiments, sample 48 is a good experimental sample. Samples 46-47 show a gradual transition from sample 45 to sample 48.

[0198] Table 9 shows examples of glass (samples 49-54)

[0199] Table 9.

[0200]

[0201]

[0202]

[0203] Table 10 shows examples of glass (samples 55-60) Table 10.

[0204]

[0205]

[0206]

[0207] Table 11 shows examples of glass (samples 61-66) Table 11.

[0208]

[0209]

[0210]

[0211] Table 12 shows examples of glass (samples 67-71) Table 12.

[0212]

[0213]

[0214] The elastic modulus values ​​of the glasses provided by the present disclosure are at least 1% higher than the elastic modulus values ​​of Astra glasses, and the SOC values ​​are at least 1% lower than the SOC values ​​of Astra glasses. The annealing points of these glasses are also 5°C higher than the annealing points of Astra glasses, which will be beneficial to the overall TPV (total pitch variation).

[0215] refer to Figure 1 , the stress optical coefficient (SOC) decreases with the increase of RO / Al2O3 ratio. Figure 2 , the elastic modulus tends to increase with the increase of RO / Al2O3 ratio. Figure 3 , which shows the relationship between SOC and elastic modulus, the elastic modulus tends to increase as the SOC decreases.

[0216] The glass and composition provided by the present disclosure have significant advantages. For example, the glass composition exhibits desired physical and chemical properties, such as an improved annealing point (e.g., above 775°C), an improved elastic modulus, a reduced stress optical coefficient (SOC), and a desired liquidus viscosity. The glass composition is suitable for use as a substrate in a flat panel display device such as an active matrix liquid crystal display (AMLCD) with ultra-high resolution under, for example, 8K display technology.

[0217] In another aspect, the present disclosure provides an article comprising the glass or glass composition described herein. For example, a substrate for a liquid crystal display includes the glass or glass composition described herein.

[0218] In another aspect, the present disclosure provides a flat panel display device comprising at least one sheet comprising glass as described herein. Such a device may include a polysilicon thin film transistor.

[0219] In another aspect, a method for producing a glass or glass composition as described herein is provided. Such a method comprises at least one step of mixing and melting raw materials in mole percentages based on oxides to provide the oxides. Such a method may also comprise making a sheet comprising the glass composition by a down-drawn sheet manufacturing process or a fusion process.

[0220] Although the subject matter has been described in terms of exemplary embodiments, it is not limited thereto. Rather, the appended claims should be interpreted broadly to include other variations and embodiments that may be made by those skilled in the art.

Claims

1. A glass comprising the following substances in molar percentages based on oxides: SiO2: 68.86-70.87; Al2O3: 10.55-13.06; B2O3: 0.1-2.29; MgO: 4.82-6.4; CaO: 5.31-7.35; SrO: 0.3-3.74; and BaO: 1.5-4.64, wherein the glass is substantially alkali-free, defined by a combined concentration of Li2O, Na2O and K2O of less than 0.1 mol.%, wherein the ratio of RO / Al2O3 is in the range of 1.39 to 1.83, and RO is the sum of the molar percentages of MgO, CaO, SrO and BaO, and The stress optical coefficient (SOC) of the glass is in the range of 27.70 to 29.

70.

2. The glass of claim 1, wherein B2O3 is in the range of 0.1 to 1.98 mole percent.

3. The glass of claim 1, wherein B2O3 is in the range of 0.5 to 1.90 mole percent.

4. The glass of claim 1, wherein the ratio of RO / Al2O3 is in the range of 1.47 to 1.

83.

5. The glass according to claim 1, further comprising 0.01 mol.% to 0.4 mol.% of a chemical fining agent, wherein the chemical fining agent is selected from SnO2, As2O3, Sb2O3, Fe2O3, CeO2, MnO2, F, Cl, Br or any combination thereof.

6. The glass of claim 6, wherein the chemical fining agent comprises 0.08 mol. % to 0.13 mol. % SnO2.

7. The glass of any one of claims 1 to 6, wherein the glass has an annealing point in the range of 775°C to 810°C.

8. The glass of any one of claims 1 to 6, wherein the glass has an annealing point in the range of 780°C to 810°C.

9. The glass of any one of claims 1 to 6, wherein the glass has an annealing point in the range of 785°C to 810°C.

10. The glass of any one of claims 1 to 6, wherein the glass has an annealing point in the range of 780°C to 791°C.

11. The glass of any one of claims 1 to 6, wherein the glass has an elastic modulus in the range of 82.47 GPa to 84.90 GPa.

12. The glass of any one of claims 1 to 6, wherein the glass has a stress optical coefficient (SOC) in the range of 27.70 to 29.

70.

13. A glass comprising the following substances in mole percentages on an oxide basis: SiO2: 68.86-70.87; Al2O3: 10.55-13.06; B2O3: 0.1-1.98; MgO: 4.82-6.4; CaO: 5.31-7.35; SrO: 0.3-3.74; and BaO: 1.5-4.64, wherein the glass is substantially alkali-free, defined by a combined concentration of Li2O, Na2O and K2O of less than 0.1 mol.%, wherein the ratio of RO / Al2O3 is in the range of 1.39 to 1.83, and RO is the sum of the molar percentages of MgO, CaO, SrO and BaO, and The elastic modulus of the glass is in the range of 82.47 GPa to 84.90 GPa, and the stress optical coefficient (SOC) is in the range of 27.70 to 29.

70.

14. The glass of claim 13, wherein the ratio of RO / Al2O3 is in the range of 1.47 to 1.

83.

15. The glass according to claim 13, further comprising 0.08 mol.% to 0.13 mol.% SnO2 as a chemical fining agent.

16. The glass of any one of claims 13 to 15, wherein the glass has an annealing point in the range of 775°C to 810°C.

17. The glass of any one of claims 13 to 15, wherein the glass has an annealing point in the range of 780°C to 791°C.

18. An article comprising the glass according to any one of claims 1 to 6. 19 . A liquid crystal display substrate, comprising the glass according to claim 1 .

20. A flat panel display device comprising at least one plate comprising the glass according to any one of claims 1 to 6, and a polysilicon thin film transistor.

21. A method for producing the glass of any one of claims 1 to 6, comprising mixing and melting raw materials in mole percentages on an oxide basis.

22. The method of claim 21, further comprising manufacturing the sheet comprising glass by a down-drawn sheet manufacturing process or a fusion process.

Citation Information

Cited By

  • Composite fluxing agent, aluminoborosilicate glass as well as preparation method and application of aluminoborosilicate glass

    CN121913699A